Performance of agricultural factors on yield of sweet corn (Zea mays L. Saccharata ) - A review - Sidahmed, Hajer Mohamed Ibrahim; Illés, Árpád; ALmahi, Ali; Nagy, János (Acta Agraria Debreceniensis, 2024)
Sweet corn producers and industries require more reliable cultivars which could be accomplished by hybrid breeding. However, progressive phenological growth may be affected by different factors. In this paper, we analyze the key factors that determine the growth and yield of sweet corn. Environmental factors such as temperature and photoperiod were strong determinants of dates of flowering and harvest which are often crucial to yield in diverse climates and agricultural systems, besides the country’s pedological conditions, especially soil fertility, affected phenological development. The effectiveness of fertilization in improving sweet corn growth performance was significantly influenced by the soil characteristics, the water supply, the genotype, and the agrotechnological factors. Therefore, genetic improvement of hybrids should be incorporated into the climate and soil elements to stabilize sweet corn yields in various agroecosystems. Decisions made in the sowing period are very significant, as up to 30% of the obtained yield may depend on making the proper choice. Deviation from the optimum date (either early or late sowing) may decrease yield. When deciding about the sowing date of maize, one needs to consider climate, soil quality, geographical location, temperature, weed infestation, sowing seed quality, and the ripening time of the hybrid to be produced.